Program Citizen's Charter terkait Pembangunan Sanitasi IPAL (Instalasi Pengelolaan Air Limbah) Domestik Komunal dalam Rangka Mewujudkan Sustainable Development - Wedar Purboningtyas (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2014)
Abstract: Citizen 's Charter Programme Related Sanitation Development WWTP ( Waste Water ) Domestic Communal In Order To Achieve Sustainable Development . This study was conducted to see the impact of the end of the communal development of domestic wastewater sanitation related programs of citizen 's charter in the health field . Development of domestic sanitary communal WWTP is intended for development over the long term . Blitar government take sanitation devoted to the management of domestic waste water because the government saw many people are still around , especially in the region and sub- districts Sananwetan lifestyle Kepanjenkidul have less clean and healthy . Therefore , the government is taking this way to address problems of domestic waste in the community in the district and sub-district Sananwetan Kepanjenkidul to be menelola domestic waste that they incur . This study used a qualitative approach and descriptive data analysis model of Miles Hubberman . The result is the construction of a communal domestic wastewater sanitation diseases caused kkarena less clean and healthy living can be resolved . And can change the pattern of life for the community towards a cleaner and healthier . Although people have behaved healthy and clean , but the government should also continue to monitor the management and treatment procedures of domestic sanitary communal WWTP itself to be used in a long period of time in accordance with the original purpose. Keywords : Domestic WWTP Communal Sanitation Development , The Final Results from Program Citizen 's Charter the field of Health , Long Term Regional Development Plan of Blitar . Bottom of Form Abstrak: Program Citizen’s Charter Terkait Pembangunan Sanitasi IPAL (Instalasi Pengelolaan Air Limbah) Domestik Komunal Dalam Rangka Mewujudkan Sustainable Development. Penelitian ini dilakukan untuk melihat dampak akhir pembangunan sanitasi IPAL domestik komunal terkait program citizen’s charter pada bidang kesehatan. Pembangunan sanitasi IPAL domestik komunal ini merupakan pembangunan yang ditunjukan untuk kurun jangka panjang. Pemerintah Kota Blitar mengambil sanitasi yang dikhususkan pada pengelolaan air limbah domestik karena pemerintah melihat masih banyaknya masyarakat sekitar khususnya diwilayah kecamatan Sananwetan dan kecamatan Kepanjenkidul memiliki pola hidup kurang bersih dan sehat. Oleh sebab itu, pemerintah mengambil cara ini untuk menanganni masalah limbah rumah tangga yang ada di masyarakat di kecamatan Sananwetan dan kecamatan Kepanjenkidul agar bisa menelola limbah domestik yang mereka keluarkan. Penelitian ini menggunakan pendekatan kualitatif deskriptif dan analisis data model Miles Hubberman. Hasilnya dengan pembangunan sanitasi IPAL domestik komunal berbagai penyakit yang disebabkan kkarena hidup kurang bersih dan sehat dapat teratasi. Serta dapat merubah pola hidup masyarakat untuk kearah yang lebih bersih dan sehat. Meskipun masyarakat sudah berperilaku hidup sehat dan bersih, tetapi pemerintah juga harus terus memantau tata cara pengelolaan dan perawatan dari sanitasi IPAL domestik komunal itu sendiri agar dapat digunakan dalam jangka waktu yang lama sesuai dengan tujuan awal. Kata kunci: Pembangunan Sanitasi IPAL Domestik Komunal, Hasil Akhir Program Citizen’s Charter Dibidang Kesehatan, Rencana Pembangunan Jangka Panjang Daerah Kota Blitar.